Interobserver Variability in Squamous Cell Carcinoma of the Penis: Analyzing the Degree of Differentiation by Pathologic Subspecialty With Correlation to Pathologic Stage. (21st September 2018) - Mullane, Patrick; Willis, Brian; Dimarco, Michelle; Plantinga, Laura; Stoff, Benjamin; Master, Viraj; Osunkoya, Adeboye; Ellis, Carla
Abstract: Objectives: Assessment of the risk of metastatic spread and subsequent treatment of inguinal lymph node metastases are the most important factors for survival among penile cancer patients. Tumor grading is often used as a prognostic indicator for inguinal lymphadenectomy. Tumor grading in squamous cell carcinoma (SCC) of the penis has been based on a four-tiered system (G1-4) that shows increased interobserver variability (IOV) (kappa = 0.34). We sought to determine if a three-tiered system based on degree of differentiation and evaluated by pathologists with varying subspecialty expertise might result in decreased IOV. Methods: Thirty-four cases of SCC of the penis were identified and initially reviewed by one observer who selected the most representative section. All representative sections were reviewed by board-certified pathologists with expertise in gynecologic, dermatologic, or urologic pathology. Each observer applied only one of each degree of differentiation (well = 1, moderate = 2, or poor = 3). We then assigned stage groups as follows: 0is-I = A, IIa-IIIb = B, and IV = C. "Accuracy" was defined when 1 = A, 2 = B, and 3 = C. IOV was calculated using kappa statistics. Results: The average age was 61 years (range, 29–83). Of the 34 cases, 11 cases were stage group A, 21 were stage group B, and 2 were stage group C. In our three-tiered system, the gynecologic expert showed the most accuracy at 58.8% compared to urology (44.1%) and dermatology (38.2%). Agreement (when all three observers agreed on the degree of differentiation) occurred in 15 of 34 (44%) cases, resulting in a kappa coefficient of 0.35. Conclusion: Despite a simplified three-tiered system, IOV of penile SCC was relatively similar to that seen in the four-tiered system in this small cohort. Larger cohorts of observers in a single subspecialty may show reduced IOV.